Bovine coronavirus mRNA replication continues throughout persistent infection in cell culture. - Hofmann, M A (1990)
The existence of viral mRNA replicons was demonstrated in cells infected with the bovine coronavirus by showing a minus-strand counterpart and a corresponding replicative intermediate for each subgenomic mRNA species. mRNA replication is thus a universal property of coronaviruses, since this is now the third coronavirus for which it has been demonstrated. During the acute phase of infection (first 48 h), minus and plus strands accumulated at the same rate initially, but maximal accumulation of minus strands peaked earlier than that for plus strands, indicating that minus- and plus-strand levels are differentially regulated. In addition, packaged (input) mRNAs appeared to serve as templates for their own early replication. mRNA replication continued throughout establishment and maintenance of persistent infection (studied for 120 days), which is consistent with our hypothesis that mRNA replication contributes mechanistically to virus persistence. A replication-defective (potentially interfering) species of RNA existed transiently (beginning at day 2 and ending before day 76 postinfection), but because of its transient nature it cannot be considered essential to the long-term maintenance of virus persistence.